2000
DOI: 10.1002/1521-4141(2000)30:8<2235::aid-immu2235>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani promastigotes evade the activation of mitogen-activated protein kinases p38, c-Jun N-terminal kinase, and extracellular signal-regulated kinase-1/2 during infection of naive macrophages

Abstract: The protozoan parasite Leishmania fails to activate naive macrophages for proinflammatory cytokines production, and selectively impairs signal transduction pathways in infected macrophages. Because mitogen‐activated protein kinases (MAPK)‐ and NF‐κB‐dependent signaling pathways regulate proinflammatory cytokines release, we investigated their activation in mouse bone marrow‐derived macrophages (BMM) exposed to Leishmania donovani promastigotes. In naive BMM, the parasite failed to induce the phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 56 publications
9
95
0
3
Order By: Relevance
“…Studies of I B␣ degradation or I B␣ mRNA expression as a reliable indicator of NF-B activation have yielded contradictory results. Indeed, whereas L. donovani promastigotes do not induce I B degradation in murine bone marrow-derived macrophages, an increase in I B mRNA expression was detected by in situ hybridization in the footpads of L. donovani-infected mice (14,39). Our results showing that Leishmania induced NF-B activation are in accordance with the latter findings.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies of I B␣ degradation or I B␣ mRNA expression as a reliable indicator of NF-B activation have yielded contradictory results. Indeed, whereas L. donovani promastigotes do not induce I B degradation in murine bone marrow-derived macrophages, an increase in I B mRNA expression was detected by in situ hybridization in the footpads of L. donovani-infected mice (14,39). Our results showing that Leishmania induced NF-B activation are in accordance with the latter findings.…”
Section: Discussionmentioning
confidence: 87%
“…L. donovani has also been reported to fail to induce phosphorylation of p38MAPK, c-Jun N-terminal kinase, and extracellular signal-regulated kinase 1/2. The same report also showed that L. donovani infection does not lead to degradation of I B␣ (39). However, no previous studies have dealt with the direct effect of Leishmania amastigote infection on NF-B activation in human macrophages.…”
mentioning
confidence: 99%
“…This complex signaling pathway could either be activated or suppressed leading to the induction of gene products that favor parasite survival. While L. donovani inhibits EKR1/2, p38MAPK, and JNK activation in naïve macrophages leading to the suppression of pro-inflammatory cytokine production (Privé & Descoteaux, 2000), L. amazonensis activates ERK1/2 leading to the production of IL-10, a cytokine that contributes to parasite growth (Yang, Mosser, & Zhang, 2007). Mechanisms behind MAPK inactivation by Leishmania have been extensively studied.…”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 99%
“…This effect was shown to be mediated by the LPG expressed on the parasite surface. However, there are contradictory observations that have found that infection with L. donovani promastigote does not result in the activation of ERK (Prive and Descoteaux, 2000), thus calling into question the role of ERK in the suppression of IL-12 by these parasites. In studies with L. amazonensis parasites, we have found that although ERK and the other MAP kinases are activated by infection with the promastigote form, inhibition of the activation of these MAP kinases does not reverse suppression of IL-12 during infection (unpublished data).…”
Section: Inhibition Of Il-12 Productionmentioning
confidence: 99%